UN High-Level Pledging Events as a Tool to Mobilise Humanitarian Financing for African Countries - SHATALOV Artemii Sergeevich (Ученые записки Института Африки Российской академии наук)
This article studies UN high-level pledging events as a tool for mobilising funds for humanitarian assistance. The author traces the evolving approaches of the UN Office for Coordination of Humanitarian Affairs (OCHA) towards such conferences, including their thematic and financial part. It highlights the increasing convening of “state-specific” meetings, and while until 2022 the focus was on a limited number of protracted humanitarian crises (Afghanistan, Syria, Yemen), in 2023‒2024, it shifted towards regional crises in Africa. The article stresses that, unlike donor conferences with limited participation, UN high-level pledging events are organised in line with the Guiding Principles of Humanitarian Assistance enshrined in the fundamental UN General Assembly resolution 46/182 of 1991, including the key role of the affected state in organising and coordinating humanitarian aid for its own population as well as the principles of neutrality and impartiality. The study analyses the cases of UN donor meetings for Sudan and Ethiopia and demonstrates that, while the financial outcome of such conferences might be dubious, they can be quite effective in countering the donors’ politicising humanitarian assistance. Furthermore, they give the affected state a platform where it can provide the international community with its own data on the humanitarian situation in the country in order to prevent launching “humanitarian interventions” or some cross-border mechanisms, including those under UN Security Council resolutions. In this regard, the author concludes that multilateral humanitarian meetings are primarily an instrument of political interaction between a donor and a recipient of humanitarian aid.